Light histories influence the impacts of solar ultraviolet radiation on photosynthesis and growth in a marine diatom, Skeletonema costatum - Guan, W. C.; Gao, K. S.; 高坤山 (2008)
Phytoplanktonic species acclimated to high light are known to show less photoinhibition. However, little has been documented on how cells grown under indoor conditions for decades without exposure to UV radiation (UVR, 280-400 nm) would respond differently to solar UVR compared to those in situ grown under natural solar radiation. Here, we have shown the comparative photosynthetic and growth responses to solar UVR in an indoor-(IS) and a naturally grown (WS) Skeletonema costatum type. In short-term experiment (<1 day), phi(PSII) and photosynthetic carbon fixation rate were more inhibited by UVR in the IS than in the WS cells. The rate of UVR-induced damages of PSII was faster and their repair was significantly slower in IS than in WS. Even under changing solar radiation simulated for vertical mixing, solar UVR-induced higher inhibition of photosynthetic rate in IS than in WS cells. During long-term (10 days) exposures to solar radiation, the specific growth rate was much lower in IS than WS at the beginning, then increased 3 days later to reach an equivalent level as that of WS. UVR-induced inhibition of photosynthetic carbon fixation in the IS was identical with that of WS at the end of the long-term exposure. The photosynthetic acclimation was not accompanied with increased contents of UV-absorbing compounds, indicating that repair processes for UVR-induced damages must have been accelerated or upgraded. (C) 2008 Elsevier B.V. All rights reserved.